Based on bibliometric visual analysis, the current status and development trends of research on complications after cholecystectomy - Cheng, Xiangjie; Hao, Fengchen; Wang, Zhan (Frontiers in Surgery, 2025)
BackgroundCholecystectomy is a common procedure for treating gallbladder diseases such as cholecystitis and cholelithiasis. Potential complications include bile leakage, infection, bleeding, bile duct injury, and residual bile duct stones, which can significantly affect recovery, quality of life, and overall health. Research on these postoperative complications has gained increasing attention in recent years.ObjectiveThis study aims to systematically review international literature on cholecystectomy postoperative complications published between 2004 and 2023. The goal is to explore current research trends, hotspots, and developments, providing valuable insights for preventing and managing these complications.ResultsA total of 6,890 articles were retrieved from the WoS database, including 6,173 original research papers and 717 reviews. The publication volume has steadily increased over the past 20 years. The top three countries in publication volume are the U.S., China, and Italy. Sandblom G is the most prolific author, and Harvard University is the most cited institution. The highest volume of publications is in the Surgery field, with Surgical Endoscopy and Other Interventional Techniques being the leading journal. Recent research hotspots include safety, delayed cholecystectomy, guidelines, and postoperative complications.ConclusionThis bibliometric analysis highlights the steady growth of research on postoperative complications of cholecystectomy since 2004, focusing on complication management, prevention, and laparoscopic cholecystectomy risks. Future research should prioritize improving surgical safety, developing delayed cholecystectomy strategies, and creating clinical guidelines to support ongoing advancements in the field.